THE CONTRIBUTION OF ALAWIYYIN SCHOLARS IN GROUNDING ISLAM IN THE ARCHIPELAGO IN THE 15TH-16TH CENTURY AD - Dzulkifli Hadi Imawan; Labib Najib Abdullah Ghaleb (Akademika : Jurnal Pemikiran Islam, 2021)
This study explains the contribution of Alawiyyin Ulama in the Islamization of the archipelago in the 15-16 century AD. They have contributed a lot to the intellectual-spiritual development of Islam in Islamic civilization in the archipelago. But really, their role is not widely written by historians considering the many classical scientific sources that recorded their history. Therefore, this study aims to provide new facts in revealing their contribution in spreading Islam in the archipelago through various classical literatures that record their contribution to the Islamization of the archipelago. This research was conducted using literature study; with historical analysis to find historical data and facts about the contribution of Alawiyyin scholars in the Islamization of the archipelago in the 15-16 century AD. The results of this study explain that the contribution of the Alawiyyin in the Islamization of the archipelago can be seen from their efforts to spread Islam so that civilization is born. Islam in the Archipelago. They also contributed to grounding the Ahlussunnah wa Jama'ah, the Syafii Madzhab, and Sunni Sufism in the archipelago with wisdom and wisdom.